2000
DOI: 10.1128/iai.68.11.6289-6293.2000
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis in Mice Devoid of Tumor Necrosis Factor and Response to Treatment

Abstract: Tumor necrosis factor (TNF)-deficient mice were challenged with Leishmania donovani to characterize TNF in the response of visceral intracellular infection to antileishmanial chemotherapy. In wild-type controls (i) liver infection peaked at week 2 and resolved, (ii) discrete liver granulomas developed at weeks 2 to 4 and involuted, and (iii) leishmanicidal responses to antimony (Sb), amphotericin B (AmB), and miltefosine were intact. In TNF knockout (KO) mice (i) initial liver infection was unrestrained, plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
2
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 35 publications
(54 reference statements)
4
104
2
4
Order By: Relevance
“…Also, we demonstrated that the rSMT plus MPL ® -SE vaccine induced Ag-specific T-cells which are capable of producing multiple Th1-type cytokines in response to Ag recall. All of TNF-α, IL-2 and IFN-γ are involved in protection against VL [4,5,34]. As TNF-α synergizes with IFN-γ in killing Leishmania parasites [35], induction of Ag-specific T-cells capable of producing multiple cytokines upon Ag recall might be more beneficial for control of Leishmania infection than those producing single cytokine, and such induction may be a good indicator whether a vaccine composed of Ag and adjuvant is protective against leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we demonstrated that the rSMT plus MPL ® -SE vaccine induced Ag-specific T-cells which are capable of producing multiple Th1-type cytokines in response to Ag recall. All of TNF-α, IL-2 and IFN-γ are involved in protection against VL [4,5,34]. As TNF-α synergizes with IFN-γ in killing Leishmania parasites [35], induction of Ag-specific T-cells capable of producing multiple cytokines upon Ag recall might be more beneficial for control of Leishmania infection than those producing single cytokine, and such induction may be a good indicator whether a vaccine composed of Ag and adjuvant is protective against leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…In common with other intracellular pathogens, cellular immune responses are critical for protection against leishmaniasis. Th1 immune responses play an important role in mediating protection against Leishmania, including roles for CD4 + and CD8 + T cells, IFN-γ, IL-12, TNF-α and NO, whereas inhibitory effects have been reported for IL-10 and TGF-β [1][2][3][4][5][6][7][8][9]. Effective immunization against leishmaniasis in animal models can be effected by delivery of Agencoding DNA vectors [10][11][12] or by administration of proteins formulated with Th1-inducing adjuvants including IL-12 [13][14][15] or TLR ligands such as CpG oligonucleotides [16][17][18] and monophosphoryl lipid A [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…IL-12 likely drives the Th1 cell-associated mechanism and induces IFN-␥, both cytokines direct T cells and blood monocytes into granulomas at parasitized tissue foci, and IFN-␥ activates effector monocytes and macrophages to kill intracellular parasites (6,23,24,34). Endogenous IL-12 and IFN-␥, as well as other cytokines (1,29), are also required for the leishmanicidal effect of pentavalent antimony (Sb), used as conventional chemotherapy for visceral leishmaniasis (23,27,28).…”
mentioning
confidence: 99%
“…TNF-a production in response to miltefosine was completely impaired in PAF receptor-deficient macrophages. Although TNF-a was previously shown to be a strong antileishmanial cytokine (25,26), the involvement of TNF-a in miltefosine-induced PAF receptor-mediated antileishmanial function was never implicated. In this article, our observations report for the first time, to our knowledge, that PAF receptor is involved in miltefosine-induced TNF-a production and subsequent antileishmanial functions.…”
Section: An Anti-paf Receptor Ab Inhibits Miltefosine-induced Leishmamentioning
confidence: 99%